Clostridioides difficile em crianças com diarreia atendidas em hospital pediátrico em Fortaleza, Ceará - Nogueira, Hildênia Baltasar Ribeiro (2019)
This study aimed to characterize Clostridioides difficile (C. difficile) infection in children with diarrhea seen at a Tertiary Pediatric Hospital in Fortaleza, Ceará. An observational cross-sectional study was conducted from January 2015 to December 2017 in children and adolescents with diarrhea to investigate C. difficile infection (CDI) by detecting ELISA positivity for toxin A and/or B, culture on Cycloserine, Cefoxitin, Fructose (CCFA) agar and anaerobic incubation, identification of strains with phenotypic analysis and detection of toxin and tpi genes fragment by conventional PCR and molecular identification analysis by PFGE, and PCR ribotyping. Antimicrobial susceptibility was verified by E-test. Fifty-six samples were included. Toxin positivity (ELISA) and/or isolation of C. difficile by culture were found in 17/56 samples (30.4%). C. difficile isolation percentage by culture was 35% (6/17) and 4 isolates were obtained: 046 (HIAS 01), 106 (HIAS 15), 002 (HIAS 54), 012 (HIAS 58), with toxigenic profile (PFGE): tpi +, tcdA +, tcdB +, cdtB-, no tcdC, deletions, one NAP11 and 3 new pulsotypes: HIAS 01 (1174), HIAS 54 (NML-1234) and HIAS 58 (NML-1235) were found. All strains were sensitive to metronidazole and vancomycin. The average age was 10.5 (± 5.14). Age ranged from 15 months to 18 years. Diarrhea had an average duration of 11 days, ranging from 3 to 50 days, with mucus and blood in 41.1% (7/17). Other symptoms found were: nausea and vomiting 52.9% (9/17), fever 41.1% (7/17), abdominal pain 82.3% (14/7). The percentage of risk factors for CDI were: hospitalization 41.1% (7/17), previous use of antibiotics and proton pump inhibitors 47% (8/17). The six children in whom C. difficile isolation was performed had prior chronic disease. Appropriate guidelines for treatment and environmental hygiene have been established. In conclusion, CDI has a prevalence of 30.4% in children with diarrhea in a pediatric hospital in Ceará. The 4 toxigenic strains were from ribotypes 044, 106, 002 and 012 and sensitive to metronidazole and vancomycin. This paper highlights the importance of knowledge of C. difficile strains and ribotyping to draw a local epidemiological profile that can contribute to better clinical intervention and environmental prophylaxis